Web service quality descriptions for web service consumers - Rückert, Jürgen; Paech, Barbara (Software quality in service-oriented architectures, 2006)
Web service consumers require web service quality descriptions for a variety of tasks; to understand the quality offered, to define the quality required, to create service level agreements and to monitor the quality received from service providers. Currently, only task-specific quality description languages support these tasks. Our goal is that web service consumers should be able to fulfill all of these tasks and that quality descriptions can be applied without language barriers. Thus, quality descriptions have to be merged. This article presents the tasks of a web service consumer that deal with quality descriptions and it defines requirements for a quality description language that supports all introduced tasks. Existing web service quality descriptions are analyzed and it is checked how many of the presented tasks they fulfill.